Depressive Symptomatology and Parenting Stress: Influence on the Social-Emotional Development of Pre-Schoolers in Chile - María Pía Santelices; Francisca Tagle; Nina Immel (MDPI AG, 2021)
(1) Background: The preschool stage is a period of great psychological changes that requires the support of parents and significant adults for optimal development. Studies show that maternal mental health can be a risk factor in parenting, affecting the social-emotional development of children. (2) Methods: The present study seeks to shed light on the relation between depressive symptoms, parental stress in mothers and social-emotional development of their preschool children, using a total of 123 mother-child dyads with low Social-economic Status (SES). In mothers, depressive symptomatology and level of parental stress were evaluated, as well as social-emotional development in children. A possible mediation effect between maternal depressive symptoms and parenting stress is expected. (3) Results: The results indicate that higher levels of depressive symptoms and parenting stress in mothers relate to greater difficulties in social-emotional development of their preschool children. (4) Conclusions: These results are clinically relevant from the perspective of family therapy: Parents need support to decrease their levels of parenting stress in order not to jeopardise their children's social-emotional development.